Complexity sciences : theoretical and empirical approaches to social action - Lisboa, Manuel; Cerejo, Dalila (Cambridge Scholars Publishing, 2018)
Recent world events have forced us to develop new scientific approaches to address social dynamics currently on the verge of rupture. Social problems and drastic changes like the refugee crisis, Brexit, the recent global economic crisis, social uprisings, forced governmental collapses, and increasing inequalities have alerted social scientists to new forms of individual and collective interactions. Researchers are now struggling to develop innovative methodologies to address the current complexity of the social world. Sociocybernetics embraces this challenge by addressing the complexity of soc.